Factors associated with prognosis and survival in hospitalized adult patients diagnosed with acute myeloid leukemia at the hospital nacional dos de mayo period 2014 to 2016 - -Bromley, Nicolás J. Higueras (2019)
Introduction:Survival in patients diagnosed with Acute Myeloid Leukemia (AML) can be affected by various clinical, cytogenetic and immunophenotypic factors.Objective:To determine the characteristics of the CCU cancer screening in 08 health facilities (EESS) of Metropolitan Lima, the headquarters of the Medical Board of the FAMURP in 2017.Methods:An observational, transversal, retrospective and analytical study was carried out, based on the review of storiesClinics of all adult patients diagnosed with Acute Myeloid Leukemia, diagnosed in April 2014 to December 2016 and followed up to determine its final outcome at 2 years, associating it with the presence of mortality conditions factors. The final sample was 39 patients.Results:Of the 39 patients, 16 (41%) were older than 60 years, 23 (59%) were younger than 60 years, 13 of the patients (33%) had a Leukocyte count greater than 50,000 at diagnosis and 26 (77%). ) presented a figure of less than 50,000. 33 patients presented a Novo Leukemia (84%) and 6 (16%) presented a Leukemia secondary to a Dysplastic Myel Syndrome or some previous history of chemotherapy. Data were not obtained for all patients according to the British American British classification (FAB), Immunophenotype and Karyotype. Survival was evaluated in 3 times, at 6 months, at one year and at 2 years from the date of diagnosis, while at 6 months the overall survival of the 39 patients had been 69% (25), at 49 % (18) and at 2 years remained in the same range. Survival at 1 year and 2 years after diagnosis was obtained with the same Odds Ratio (OR) of 4.5 for the variable Leukocytes at diagnosis greater than 50 000 (95% CI: 1,008 - 20,507), considering it as a risk factor for mortality. In the survival analysis of the same variable mentioned with one year survival and two years survival was significantly lower in the group of patients with leukocytes at diagnosis greater than 50,000.Conclusion:In our study population, statistical significance was found when evaluating the Leukocyte variable at diagnosis greater than 50,000, finding it as a factor associated with 2-year mortality, with a significantly greater survival than the group of patients with Leukocytes at diagnosis less than 50. 000.   DOI:  10.25176/RFMH.v19.n1.1789